Early antiretroviral therapy is associated with better viral suppression and less HIV drug resistance after implementation of universal treatment in South Africa - Dorward, J; Drain, PK; Osman, F; Sookrajh, Y; Pillay, M; Moodley, P; Garrett, N (Mary Ann Liebert Inc., 2019)
All people living with HIV should receive antiretroviral therapy (ART), but those with CD4 counts >500 cells/mm3 at ART initiation (“early initiators”) may be less motivated to adhere to treatment, compared with those with CD4 counts <200 cells/mm3 (“late initiators”). We performed a cross-sectional analysis among HIV-positive adults who had a viral load taken at 6 months after first-line ART initiation in a South African public clinic. Retrospective HIV drug resistance testing was performed on all samples with a viral load >1,000 copies/mL. We used Poisson regression models with robust variance to evaluate associations between early ART initiation and viral suppression <40 copies/mL. We assessed HIV drug resistance using descriptive statistics. Of 390 participants enrolled between February and August 2017, 60% were women and median age was 32 years [interquartile range (IQR) 27–38]. At ART initiation, median CD4 count was 366 cells/mm3 (IQR 204–546), and 30% were early initiators with CD4 > 500 cells/mm3. In multivariable analysis, early initiators were more likely to be virally suppressed compared with late initiators (adjusted risk ratio: 1.29, 95% confidence interval: 1.13–1.46). All 18 participants with viral load >1,000 copies/mL had successful genotyping, which identified drug resistance in 14/18 (77.8%). Among early initiators, drug resistance was detected in only 1/117 (0.9%), compared with 11/93 (11.8%) among late initiators. In conclusion, among people receiving ART in a South African public clinic, early initiators had better viral suppression after 6 months and less drug resistance than late initiators, which further supports universal treatment. Clinical trials registration: NCT03066128.